2016
DOI: 10.1111/dote.12310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastroesophageal reflux disease in Moscow

Abstract: Limited data exist to determine the prevalence and clinical spectrum of gastroesophageal reflux disease (GERD) in the Russian population, which might be different from those in Western countries. This study was performed in Moscow on randomized 1065 adults aged ≥ 15 years. A validated reflux questionnaire comprising 72 questions and an additional 29 sub-questions were used. The questions assessed (heartburn and regurgitation) and related (dyspepsia, dysphagia, odynophagia and chest pain) symptoms, the triggeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
1
27
0
10
Order By: Relevance
“…Sixty-nine studies reported the duration of symptoms required to meet criteria for gastro-oesophageal reflux, with 36 using 12 months,11 24 28 29 31 32 35–37 41 42 46–48 56 62 65 67 69 70 73 74 77 79–83 86 94 100 102 104 107 111 115 6 using 6 months,19 34 38 51 71 101 11 using 3 months,23 26 33 39 40 43 44 52 60 87 109 7 using 1 month53 64 78 88 92 106 118 and 9 using 1 week 27 59 66 84 99 105 112 114 117. The prevalence of gastro-oesophageal reflux symptoms was highest in studies that used a 1-month timeframe (20.1%), but was also higher in studies that used 6 months, compared with those that used 12 months (17.6% vs 14.1%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixty-nine studies reported the duration of symptoms required to meet criteria for gastro-oesophageal reflux, with 36 using 12 months,11 24 28 29 31 32 35–37 41 42 46–48 56 62 65 67 69 70 73 74 77 79–83 86 94 100 102 104 107 111 115 6 using 6 months,19 34 38 51 71 101 11 using 3 months,23 26 33 39 40 43 44 52 60 87 109 7 using 1 month53 64 78 88 92 106 118 and 9 using 1 week 27 59 66 84 99 105 112 114 117. The prevalence of gastro-oesophageal reflux symptoms was highest in studies that used a 1-month timeframe (20.1%), but was also higher in studies that used 6 months, compared with those that used 12 months (17.6% vs 14.1%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence using this definition was 9.4% (95% CI 9.1% to 9.7%), but heterogeneity between studies remained (I 2 =98.7%, p<0.001). There were another 30 studies that used a frequency of symptoms of at least weekly for the last 12 months,11 28 29 32 36 41 46–48 56 65 67 69 70 73 74 77 79 80–83 86 94 100 102 104 107 111 115 and when these were pooled the prevalence was 14.0% (95% CI 12.1% to 16.1%), again with significant heterogeneity between studies (I 2 =99.0%, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations